2013
DOI: 10.1080/19485565.2013.774627
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Signatures May Explain the Relationship between Socioeconomic Position and Risk of Mental Illness: Preliminary Findings from an Urban Community-Based Sample

Abstract: Low socioeconomic position (SEP) has previously been linked to a number of negative health indicators, including poor mental health. The biologic mechanisms linking SEP and mental health remain poorly understood. Recent work suggests that social exposures influence DNA methylation in a manner salient to mental health. We conducted a pilot investigation to assess whether SEP, measured as educational attainment, modifies the association between genomic methylation profiles and traumatic stress in a trauma-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 74 publications
1
26
1
Order By: Relevance
“…Some of the current human EWAS that have examined mDNA alterations in PTSD are summarized in Table 2. EWAS are listed in chronological order (2010–2017) [54•, 55, 56, 57•, 58, 59•, 60, 61]. The sites with differential mDNA together with the nearest gene are reported.…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the current human EWAS that have examined mDNA alterations in PTSD are summarized in Table 2. EWAS are listed in chronological order (2010–2017) [54•, 55, 56, 57•, 58, 59•, 60, 61]. The sites with differential mDNA together with the nearest gene are reported.…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…For example, the EWAS with the largest sample size to date identified epigenetic changes related to synapic plasticity, cholinergic signaling, oxytocin signaling, and inflammatory responses [61]. Smaller studies have implicated immune and inflammatory responses [54•, 55, 59•, 60], endocrine [60] and nervous system [56, 59, 60] pathways. One study has observed differential mDNA profiles in PTSD subjects with and without childhood abuse history [57•].…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…Modeling the effects of early life stressors in animals has largely corroborated such results; exposure to maternal separation or neglect heightens stress reactivity, aggression, and other features of clinical disorders such as depression and schizophrenia [58]. Accumulating evidence not only suggests that early life environment affects relevant genes via epigenetic modifications which may serve as biomarkers for susceptible populations [9, 10], but furthermore that environmentally-induced behavioral deficits may be transmitted to subsequent generations [1113]. Determining the relative contribution of genes versus environment to the manifestation of a specific behavior is of critical importance for not only elucidating its etiology, but also guiding ongoing endeavors to identify relevant trait-specific biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Summary of 43 human-based epigenetic studies of PTSD published as of July 2017, enumerated and categorized according to relevant biological system or Epigenome-wide association (EWAS) approach: Hypothalamic-Pituitary Adrenal (HPA) Axis 105,108,116,119,139150 ; EWAS 9196,151155 ; Age-related CpGs 129,132,133 ; Serotonergic system 156,157 ; Neurotrophin 117,158 ; Dopaminergic System 159 ; Catecholaminergic system 102 ; DNA methylation machinery 160 ; Estrogen-responsive genes 114 ; Immune Function 161 ; Other 162165 .…”
Section: Figurementioning
confidence: 99%